Coupling experimental and field-based approaches to decipher carbon sources in the shell of the great scallop, Pecten maximus (L.). (1st November 2015) - Marchais, V.; Richard, J.; Jolivet, A.; Flye-Sainte-Marie, J.; Thébault, J.; Jean, F.; Richard, P.; Paulet, Y.-M.; Clavier, J.; Chauvaud, L.
Abstract: This research investigated how the carbon isotopic composition of food source (δ 13 Cfood ) and dissolved inorganic carbon (δ 13 CDIC ) influences the carbon isotopic composition of Pecten maximus shells (δ 13 Cshell ) under both experimental and natural conditions. The objectives are to better understand the relationship between P. maximus and its environment, and to specifically distinguish conditions under which calcification is influenced by respired CO2 derived from food sources versus conditions in which calcification uses inorganic carbon from seawater. Laboratory experiment investigated carbon incorporation into shell carbonates by maintaining scallops under conditions where the stable carbon isotopic composition of food sources was considerably depleted (−54‰), relative to values observed in the natural environment (−21‰). Laboratory experiment ran for 78 days under three temperature conditions, 15 °C, 21 °C and 25 °C. A survey of the environmental parameters and stable carbon isotopic composition into shell carbonate of natural population of P. maximus was also realized during the same year in the Bay of Brest, France. Data collected from both laboratory experiment and the natural environment confirmed that both δ 13 CDIC and δ 13 Cfood influence δ 13 Cshell values and that organic carbon incorporation ( CM ) averages about 10% (4.3–6.8% under experimental conditions and 1.9–16.6% in the natural environment). The shift in stable carbon isotopic composition from the uptake of depleted food sources under experimental conditions realized a marked divergence in the predicted equilibrium between calcium carbonate and ambient bicarbonate, relative to the natural environment. This offset was 1.7 ± 0.6‰ for scallops in their natural environment and 2.5 ± 0.5 and 3.2 ± 0.9‰ for scallops under experimental conditions at water temperatures of 15 °C and 21 °C, respectively. The offset of 3‰ for scallops subjected to laboratory experiment could not be explained in light of growth rate but may be related to food supply and/or temperature. Food source and temperature effects may also explain the annual variation observed in CM values measured from scallops in their natural environment. CM estimation from the natural population of P. maximus varied seasonally from around 2% at the end of winter, to 12% in summer. The seasonal variation resembles variability in the carbon isotopic composition of the food sources throughout the year with an exception at the end of winter.